Birch Bayh : Making a Difference - Blaemire, Robert (Book collections on Project MUSE., 2019)
Born in Terre Haute, Indiana, right before the Great Depression, Birch Bayh served in the Indiana General Assembly (1954-1962) and the United States Senate (1963-1981). His influence was seen in landmark legislation over his tenure. Blaemire reveals a life and career dedicated to the important issues facing Indiana and the nation, including civil rights and equal rights for women. In doing so, he profiles not only the prolific career of this remarkable senator but also an era when compromise and bipartisanship were common in Congress.-- adapted from back cover.